Effectiveness of Diabetes Self Management Education on Lifestyle in Type 2 Diabetes Mellitus Patients: A Literature Review - Kurniawan Laia; Kezia Triana; Lani Watania; Heman Pailak (Indonesian Journal of Global Health Research, 2024)
Diabetes Self-Management Education (DSME) is an act of nursing that facilitates knowledge, skills, and abilities. The purpose of DSME is to change the lifestyle of diabetic patients, especially in controlling blood glucose levels. In 2021, the International Diabetes Federation noted that the global prevalence of diabetes reached 10% (537 million people). Objective to ascertain the effectiveness of diabetes self-management education (DSME) on type 2 DM patients’ lifestyle. Thematic analysis method, a simplified approach is the method used in this literature review. The articles used were obtained through searching articles form several databases such as Google Scholar, MEDLINE, and PUBMED, using the keywords "DSME AND T2DM AND lifestyle" and "DSME AND DMT2 AND lifestyle". selection of articles using the PRISMA flow diagram. The article was analyzed using JBI Critical Appraisal Checklist tools for RCT and quasi-experiments. Based on the literature review’s results of seven articles show that diabetes self-management education (DSME) is effective for lifestyle changes in type 2 DM patients in terms of time, procedure, patient characteristics, and combination of actions. Diabetes Self-Management Education (DSME) helps the type 2 diabetes patients to modify their lifestyle.